Combination of Ozone and Ceramic Raschig Ring to Improve Efficiency of Treatment of Landfill Leachate - Huu Tap, Van; Van Tuyen, Trinh; Hoai Chau, Nguyen; Xuan Hien, Dang (Asian Journal of Chemistry, 2014)
The combination with ozone/ceramic raschig ring (O3/CRR), with three strips of surface area of the ceramic raschig ring is 356, 539 and 728 m2/m3) at a concentration of O3 is 2.882 g Hr-1 studied to improve performance of landfill leachate treatment in Nam Son site, Soc Son, Hanoi city, Vietnam. Volume of landfill leachate used for each pilot lot is 1 L. The combination of ozone and the ceramic raschig ring for landfill leachate treatment has improved significantly treating performance. In experiment with the ceramic raschig ring, surface contacting area is 728 m2/m3, performance of treatment of colour, COD and TOC has increased comparison with experiment without the ceramic raschig ring is 8, 16 and 7 % respectively. The amount of residual O3 after treating in the experiment available the ceramic raschig ring (728 m2/m3 of surface area) is also much lower than the experiment without the ceramic raschig ring. Average amount residual O3 corresponding the experiment with and without the ceramic raschig ring is 0.632 and 1.639 g respectively after 100 min of treatment. At experimental conditions available the ceramic raschig ring (728 m2/m3 of surface area), the content of O3 identified uses 4.812 Kg O3/Kg COD.